Analysis of Heat-and-Mass Transfer Conjugated Problem Solution while Forming Thin-Wall Castings - R. I. Esman; L. I. Shoub (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper contains an analysis of heat-and-mass transfer conjugated problem in case of moving of liquid melts in channels of metallic forms (moulds, dies, crystallizers etc.). Investigations of velocity profiles at various flow sections, current lines in the calculated area, pressure and viscosity fields in non-stationary state have been carried out in the paper.The paper reveals that current is of parabolic shape in the annular channel at rather large distance from a projection up and down the flow and pressure along channel section is practically unchangeable.The executed investigations of heat-and-mass transfer in the moving melt make it possible to create a data base of control parameters for development of prospective technologies  of special casting methods.